Health Education to Increase Knowledge about the Transmission of Pulmonary TB Disease at the Bandar Khalipah Community Health Center - Gurusinga, Rahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Pulmonary tuberculosis (TB) is a serious public health problem in Indonesia. The rapid spread of pulmonary TB, especially through droplets, requires good understanding from the public to reduce the risk of transmission. This Community Service (PKM) aims to increase public knowledge regarding the mechanism of pulmonary TB transmission through health education programs at the Bandar Khalipah Community Health Center. The approach used is interactive counseling which covers topics about the meaning of TB, symptoms, ways of transmission, and preventive measures. This activity is aimed at TB patients and families around the community health center. The results showed a significant increase in the participants' level of understanding after attending the counseling, based on analysis before and after the activity. This shows that structured and interactive health education is effective in increasing community knowledge about pulmonary TB transmission, thus contributing to disease prevention and control at the community level.